(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
An alternative formulae is derived for NPV. First, the equivalence of NPV formulae and the value of a special portfolio is shown and weights of special portfolio is derived by minimizing the variance of portfolio.